LAND RIGHT’S APPLICATION IN ACCORDANCE WITH THE USE OF EXISTING SPACE IN MEDAN CITY - Ahmad Budinta Rangkuti; Muhammad Yamin Lubis (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
One of the tasks of the Ministry of Agrarian and Spatial Planning/National Land Agency of the Republic of Indonesia is to provide types of land rights in each region throughout Indonesia. The purpose of this study is aimed for the institution of the National Land Agency throughout Indonesia to provide land rights based on the type of land allocation and its usage. This is a normative legal study in which data were collected through library research with the support of empirical data from the Land Agency of Medan. The allocation system, a type of land zone division system, is utilized by the Municipal Land Affairs Office of Medan to establish land rights. Building rights are granted by the Land Agency when a zone has been allocated as a trading area, although in practice there are still a lot of lands used for residential purposes. The designation system for the granting of land rights assigned by the Municipal Land Affairs Office of Medan, based on Regional Regulation No. 2 of 2015, failed to uphold justice for the people of Medan that applied for the rights to the land under their name. Therefore, a more applicable system is the existing spatial system or a system based on the land’s actual use in practice Keywords: National Land Agency, spatial planning, allocation system, land use, spatial management